Instructional feedback to support self-regulated writing in primary school - Fiskerstrand, Pernille; Gamlem, Siv M. (Frontiers in Education, 2023)
Feedback that enhances self-regulated learning when writing seems to rarely be provided in classrooms to beginner writers, although acting autonomously as a writer is crucial for the pupils' further literacy development. Effective instructional feedback should be built on dialogues where the teacher supports the pupil(s) in monitoring the text, discussing qualities and weaknesses, and enhancing reflection upon what to do next. Thus, feedback interactions that emphasize pupils' agency over their own learning processes are valued, more knowledge is needed about how to facilitate such instructional feedback interactions for elementary pupils. Therefore, the current study asks: How do teachers facilitate feedback that promotes self-regulated learning when second graders (7-year-olds) are writing in classrooms? The data consist of a thematic analysis of transcriptions from video recordings (n= 540 minutes) of four teachers' classrooms. The results show that designing instructional feedback interactions that promote self-regulated learning when second graders write are possible when teachers let go of their control, letting the pupils take agency by adopting assessment criteria, monitoring their texts, and expressing self-generated feedback, as well as applying help-seeking strategies while confirmed by their high expecting teachers.